Everything I learned about racism I learned in school - Jewell, Tiffany (Versify, an imprint of HarperCollins Publishers, 2024)
From preschool to higher education and everything in between, Everything I Learned About Racism I Learned in School focuses on the experiences Black and Brown students face as a direct result of the racism built into schools across the United States. The overarching nonfiction narrative follows author Tiffany Jewell from early elementary school through her time at college, unpacking the history of systemic racism in the American educational system along the way. Throughout the book, other writers of the global majority share a wide variety of personal narratives and stories based on their own school experiences. Everything I Learned About Racism I Learned in School provides young folks with the context to think critically about and chart their own course through their current schooling -- and any future schooling they may pursue.